Cyclooxygenase‐2 expression is associated with infiltration of inflammatory cells in oral and skin canine melanomas. (3rd May 2020) - Silveira, Tatiany L.; Veloso, Emerson S.; Gonçalves, Ivy N. N.; Costa, Renato F.; Rodrigues, Michele A.; Cassali, Geovanni D.; Del Puerto, Helen L.; Pang, Lisa Y.; Argyle, David J.; Ferreira, Enio
Abstract: Melanoma is a fast‐growing tumour in dogs and represents 7% of the total malignant neoplasms from the skin and is the most common tumour found in the oral cavity. In these tumours, high expression of cyclooxygenase‐2 (COX‐2) is associated with a poor prognosis. The aim of this study was to verify if the overexpression of COX‐2 is related to the modulation of lymphocytes and if it is associated with the angiogenic and proliferative capacity of the melanoma. Canine melanoma samples (n = 85) were analysed by immunohistochemistry to detect the expression of S‐100, Melan‐A, PNL‐2, COX‐2, Factor VIII, Ki‐67 and immune cells markers (CD3, CD4, FOXP3 and MAC387); and expression levels of MAC387, NOS and CD206 were determined by immunofluorescence. Our study showed a concurrent difference between the expression of COX‐2 and inflammatory cell infiltration: Oral melanomas showed positivity for COX‐2 in 34% of the cases and this expression was associated with CD3 positivity in the inflammatory infiltrate and angiogenesis; whereas cutaneous melanomas presented positivity for COX‐2 in 42% of the cases and this expression was associated with positive staining for CD3, CD4, FOXP3 and MAC387. These markers are associated with inflammatory cells, angiogenesis and proliferation. Interestingly, melanomas were highly infiltrated by FOXP3+ cells, this is related to angiogenesis, whereas CD3, CD4 and MAC387 expression was only associated with cutaneous melanomas. The macrophage profile analysis showed that both oral and cutaneous melanomas with low COX‐2 expression have an M1 phenoptype, whereas the cases with high COX‐2 expression demonstrate a hybrid M1/M2 profile pattern. We concluded that the COX‐2 is overexpressed in 42% of cutaneous melanomas and in 34% of oral melanomas, with a direct association with angiogenesis, proliferation, and intratumoral lymphocyte infiltration. We propose that COX‐2 is a key regulator of immune cell infiltration and may drive tumour associated macrophage activation.